Share

## Consider the following pair of equations: y = x + 4 y = −5x − 2 Explain how you will solve the pair of equations by substitution. Show all t

Question

Consider the following pair of equations: y = x + 4 y = −5x − 2 Explain how you will solve the pair of equations by substitution. Show all the steps and write the solution in (x, y) form.

in progress
0

Mathematics
2 months
2021-08-01T03:10:21+00:00
2021-08-01T03:10:21+00:00 2 Answers
2 views
0
## Answers ( )

Answer:(-1, 3)

Step-by-step explanation:to solve using substitution, you have to know the value of either x or y. in this example, they gave you the value of y already: y=x+4.

this means you can substitute the y for (x+4). if we substitute y for (x+4) in the equation y=-5x-2, we get this:

(x+4)=-5x-2

then solve for x

6x=-6

so x=-1

since we know the x value, we can solve for y

y=x+4

y=-1+4

y=3

so the final answer is (-1, 3)

Answer:(- 1, 3 )

Step-by-step explanation:Given the 2 equations

y = x + 4 → (1)

y = – 5x – 2 → (2)

Substitute y = x + 4 into (2)

x + 4 = – 5x – 2 ( add 5x to both sides )

6x + 4 = – 2 ( subtract 4 from both sides )

6x = – 6 ( divide both sides by 6 )

x = – 1

Substitute x = – 1 into either of the 2 equations and evaluate for y

Substituting into (1)

y = – 1 + 4 = 3

solution is (- 1, 3 )